Evidence-based AGIHO guideline update on prophylaxis of infectious complications with granulocyte-stimulating factors (G-CSF) for the treatment of adult patients with cancer - Sandherr, Michael; Schalk, Enrico; Heinz, Werner J.; Köhler, Philipp; Krause, Stefan; Liss, Blasius; Kausche, Lea; Link, Hartmut; Mellinghoff, Sibylle C.; Schmidt-Hieber, Martin; Schuelper, Nikolai; Spiekermann, Karsten; et al. (European Journal of Cancer, 2026)
Introduction Febrile neutropenia, a common complication of systemic antineoplastic therapy, varies in risk depending on malignant disease, treatment, and patient factors. The risk increases with the depth and duration of neutropenia and can be reduced with prophylactic use of G-CSF. International guidelines are conflicting in several aspects and do not reflect all patient groups. We therefore updated the 2014 Infectious Diseases Working Party (AGIHO) guideline of the German Society of Hematology and Medical Oncology (DGHO) on evidence-based recommendations for the use of G-CSF in patients with cancer. Materials and Methods After a systematic literature search from January 2014 to December 2024 on PubMed and Medline several consensus meetings were held by an expert panel of the AGIHO to evaluate, discuss and consent on the level of evidence and strength of recommendation for the use of G-CSF in patients with cancer based on ESCMID criteria. Results Results from eligible (randomized) studies were grouped in evidence tables. Recommendations for different entities, risk groups, new G-CSF formulations and emerging strategies in immunotherapy were set up and put into comparison to 2014. Discussion Comprehensive literature search and expert panel consensus confirm most of the key recommendations of 2014. New recommendations on the use of G-CSF in immunotherapy settings provide insight and support for day-by-day clinical decision making in the care of patients with cancer.
CRIS-Team Scopus Importer:2026-02-06
Keywords: Acute leukemia; Biosimilar; Cancer; Efbemalenograstim alfa; Febrile neutropenia; G-CSF; Granulocyte colony-stimulating factor; Infection; Lymphoma; Neutropenia; Supportive care